2022
DOI: 10.1158/0008-5472.can-21-1807
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Canonical Wnt Signaling Primes Noncanonical Signaling through ROR1 in Metastatic Castration-Resistant Prostate Cancer

Abstract: Wnt signaling driven by genomic alterations in genes including APC and CTNNB, which encodes β-catenin, have been implicated in prostate cancer development and progression to metastatic castration-resistant prostate cancer (mCRPC). However, nongenomic drivers and downstream effectors of Wnt signaling in prostate cancer and the therapeutic potential of targeting this pathway in prostate cancer have not been fully established. Here we analyzed Wnt/β-catenin signaling in prostate cancer and identified effectors di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Other classical tumorigenic pathways, such as Wnt signaling pathway (KEGG:04310, adjusted p-value = 3.48e-4) and TGF-beta signaling pathway (KEGG:04350, adjusted p-value = 3.30e-5) appear also enriched. In this regard, recent studies analyzed the involvement of Wnt signaling in the proliferation of prostate cancer cells (Ma et al 2022; Wei et al 2022), as well as the involvement and TGF-beta signaling (Natani et al 2022; Xi et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Other classical tumorigenic pathways, such as Wnt signaling pathway (KEGG:04310, adjusted p-value = 3.48e-4) and TGF-beta signaling pathway (KEGG:04350, adjusted p-value = 3.30e-5) appear also enriched. In this regard, recent studies analyzed the involvement of Wnt signaling in the proliferation of prostate cancer cells (Ma et al 2022; Wei et al 2022), as well as the involvement and TGF-beta signaling (Natani et al 2022; Xi et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that WNT-pathway activation is associated with higher Gleason grades and PSA levels [ 13 ]. In addition, aberrant activation of the WNT pathway is causative to multiple cancer progression, which may be caused by mutations of pathway components or dyshomeostasis of autocrine/paracrine signaling [ 31 , 34 , 35 ]. Among them, functional mutations in WNT pathway components have been demonstrated to be important for progression and NHT resistance in mCRPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In other word, upstream components of the pathway may be responsible for the high frequency of WNT signal activation besides somatic mutations. Emerging evidence show WNT3A [ 37 , 38 ], WNT16B [ 39 ] and WNT5A [ 34 ] are essential in PCA for its initial, development, progression and therapy resistance, which may be autocrine or paracrine from stroma. In this study, higher WNT3A was detected in HOXB3 + tumors and was associated with higher tumor grade and stage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that Wnt/β-catenin signaling not only promotes stem cell maintenance and invasive ability in mCRPC but also potentiates noncanonical Wnt5a -ROR1 signaling [ 255 ]. The non-canonical Wnt co-receptor ROR1 is elevated in several hematological and solid malignancies, particularly chemo-refractory disease [ 255 , 256 , 257 , 258 , 259 ]. Furthermore, the anti-ROR1 blocking antibody cirmtuzumab has shown efficacy in chronic lymphocytic leukemia (CLL) and mantle cell lymphoma (MCL) trials [ 247 ].…”
Section: Targeting the Wnt Cascade To Treat Prostate Cancermentioning
confidence: 99%